Unified dashboard to monitor efficiency of online campaigns - Drobil, Jakub; Máša, Petr; Gburíková, Alžbeta; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
The thesis aims to design and implement a system for unified and automated reporting of marketing campaigns using transformation, storage and visualization tools. Specifically, it focuses on the design and implementation of a data pipeline starting from different marketing systems and consisting of an ETL tool Funnel, a BigQuery database, another transformation tool Dataform, a Workflows tool to automate their processes and finally a PowerBI visualization tool to present the processed data. The main goal of the thesis is to create automated dashboards with interactive graphs that will display data from different marketing systems in one place and with which the overall performance of individual marketing campaigns can be monitored. The theoretical part of the thesis introduces the reader to the world of digital marketing and describes how it works. It also discusses the current state of research on the topic of automated reporting in marketing and describes possible tools for automation along with cloud-based data storage solutions that are required for automated data processing. The practical part of the thesis is devoted to the creation of an automated reporting solution using the mentioned tools.
Vedoucí práce: Petr Máša
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses